Students’ Perception on the Implementation of Extensive Reading at Elementary School - Zelvia Dina Octavianti; Pratiwi Retnaningdyah; Ahmad Munir (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to determine students' perceptions of implementing extensive reading. The focus of this research is on the benefits and obstacles in implementing extensive reading activities. Twenty elementary school students in one of the schools in Sidoarjo were the subjects of this research. The method used in this research is a qualitative method and data collection using interview techniques. The results showed that extensive reading affects students' interest in reading because it makes students feel happy, can imagine, and increases students' knowledge and English language skills. Besides that, other findings regarding students' perceptions of obstacles in carrying out extensive reading were also revealed in this research. Some of them are students' reading motivation which is classified as low which is caused by language skills and students' lack of perseverance, as well as about the style of language used in reading texts.